Endowment effect and housing decisions - Bao, Helen X. H.; Gong, Cynthia M. (International Journal of Strategic Property Management, 2016)
Endowment effect refers to the reported gaps between willingness to accept and willingness to pay. According to prospect theory, this effect is a result of the underweighting of opportunity costs. Given the high stake involved in a typical housing transaction, endowment effect is expected to have a significant influence on housing decisions. We develop a theoretical framework to study the presence of endowment effect and its role in housing decision-making process. Three hypotheses are derived and tested through a field experiment conducted in Beijing, China. Our empirical results show that endowment effect plays an important role in the formation of judgmental biases in housing decisions. Moreover, endowment effect interacts with housing cycles. Our study highlights the application of prospect theory in the housing market; thus, it not only extends existing theoretical and empirical works in this important sector, but also clarifies consumer behavior in the emerging property market of China.First Publish Online: 14 Dec 2016